2019
DOI: 10.1109/access.2018.2890073
|View full text |Cite
|
Sign up to set email alerts
|

A Low Power All-Digital PLL With −40dBc In-Band Fractional Spur Suppression for NB-IoT Applications

Abstract: This paper proposes a low-power fractional-N all-digital PLL (ADPLL) for the narrow-band Internet-of-Things applications. Multi-step lock controlling and oscillator tuning word coarse prediction algorithms help to accelerate the locking process to less than 20 µs. A digital-to-time converter (DTC) is used with a phase prediction algorithm to minimize the detection range of the time-to-digital converter for low power consumption. The dither block is designed to improve the nonlinearity of DTC resulting in a −40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is observed from Table 4 that the proposed ADPLL has fast locking time as compared to designs in previous papers. 17,23,24 There is a reduction of 45% in the locking time and 11% reduction in the power consumption with expense of only 7% increase in the jitter as compared to architecture reported in Sahani et al 17 The proposed ADPLL has better jitter and power consumption as compared to work presented in the Tao and Heng. 22 The locking time is 1.7 μs of proposed ADPLL after postlayout simulations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is observed from Table 4 that the proposed ADPLL has fast locking time as compared to designs in previous papers. 17,23,24 There is a reduction of 45% in the locking time and 11% reduction in the power consumption with expense of only 7% increase in the jitter as compared to architecture reported in Sahani et al 17 The proposed ADPLL has better jitter and power consumption as compared to work presented in the Tao and Heng. 22 The locking time is 1.7 μs of proposed ADPLL after postlayout simulations.…”
Section: Discussionmentioning
confidence: 85%
“…The PVT variation in periodic jitter without calibration for ADPLL is shown in Figure 7. The total variation of 22.9% is 17 Tao and Heng 22 ur Rahman et al 23 Yan et al 24 De Caro et al 25 Sahani et al 26 Supply voltage (V) observed in the ADPLL without calibration. The proposed 3-bit flash TDC with resolution of 3 ps and periodic jitter of 0.46 ps is used.…”
Section: Adpll Simulation Resultsmentioning
confidence: 99%
“…However, in such applications, the battery's lifetime is limited [14]. The key specification for the frequency range is the faster lock-in time [15].…”
Section: Introductionmentioning
confidence: 99%
“…In many applications such as all-digital phase-locked loops (ADPLLs) [1], chemical sensors readout [2], frequency synthesizers [3][4][5][6], and time-of-flight (ToF) systems [7], time-to-digital converters (TDCs) play an important role by measuring a time interval. Thus far, many TDCs have been presented which have been trying to show high signal-to-noise ratio (SNR), resolution, bandwidth, and linearity.…”
Section: Introductionmentioning
confidence: 99%